Transforming food systems through inclusive agribusiness - Schoneveld, G.C. (Elsevier, 2022)
Corporations and independent experts alike consider inclusive agribusiness (IAB) instrumental to achieving sustainable and equitable development for small farmers. As businesses that productively integrate small farmers into commercial agrifood chains, IABs could help resolve some of the coordination and market and input access problems confronting many rural economies. They are therefore increasingly regarded as important private innovations to address systemic inequalities and inefficiencies within modern food systems. This article critically interrogates IAB narratives inspiring recent policy innovations. By reviewing recent IAB literature, discourse and strategies, as well as past IAB scaling experiences, it shows that IAB models such as contract farming and producer cooperatives are liable to discriminatory practices, uneven benefit capture and socio-ecological trade-offs, especially at scale. This article challenges IAB orthodoxies and the unconsidered definitions, big-business biases and value creation assumptions pervading emergent IAB policy discourse. It argues that in order for IABs to contribute to transformational change, the phenomenon deserves to be more explicitly positioned within a sustainable food systems framework. To help move the needle on IAB scholarship and policy, this article reimagines IAB along these lines.